2008
DOI: 10.1042/bc20070077
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a small region of the exportin Crm1p disrupt the daughter cell‐specific nuclear localization of the transcription factor Ace2p in Saccharomyces cerevisiae

Abstract: Background information. The CBK1 gene of Saccharomyces cerevisiae encodes a protein kinase that is a member of the NDR (nuclear Dbf2-related) family of protein kinases, which are involved in morphogenesis and cell proliferation. Previous studies have shown that deletion of CBK1 leads to a loss of polarity and the formation of large aggregates of cells. This aggregation phenotype is due to the loss of the daughter cell-specific accumulation of the transcription factor Ace2p, which is responsible for the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 42 publications
4
43
0
Order By: Relevance
“…5A). This is consistent with Ace2's previously observed localization pattern, which goes from a cytoplasmic distribution to faint nuclear localization before exhibiting strong accumulation to daughter cell nuclei (10,29,42,70). In addition, the fluorescence intensity of Ace2-AAA-GFP in the nucleus of the arrested cells was significantly lower than in the daughter nucleus of cells upon release from the arrest (Fig.…”
Section: Resultssupporting
confidence: 79%
“…5A). This is consistent with Ace2's previously observed localization pattern, which goes from a cytoplasmic distribution to faint nuclear localization before exhibiting strong accumulation to daughter cell nuclei (10,29,42,70). In addition, the fluorescence intensity of Ace2-AAA-GFP in the nucleus of the arrested cells was significantly lower than in the daughter nucleus of cells upon release from the arrest (Fig.…”
Section: Resultssupporting
confidence: 79%
“…A few minutes prior to actomyosin ring contraction, Ace2 rapidly shifts to nearly exclusive accumulation in the daughter cell's nucleus, where it remains until shortly after mother/daughter separation is complete. Ace2's localization to the daughter cell nucleus is accompanied by a corresponding reduction in its cytoplasmic concentration in both mother and daughter cells and occurs independently of the protein's ability to bind DNA (Dohrmann et al 1992;O'Conallain et al 1999;Racki et al 2000;Bidlingmaier et al 2001;Colman-Lerner et al 2001;Doolin et al 2001;Weiss et al 2002;Nelson et al 2003;Voth et al 2005;Bourens et al 2008;Mazanka et al 2008;Sbia et al 2008;Di Talia et al 2009;Mazanka and Weiss 2010;Brace et al 2011).…”
Section: Regulation Of Septation Machinery and The Cytokinetic Apparatusmentioning
confidence: 99%
“…Ace2 cannot reenter the nucleus once it is exported in G1 (Bourens et al 2008;Mazanka et al 2008;Sbia et al 2008;Mazanka and Weiss 2010), due to a multistage mechanism that traps it in the cytoplasm. This sequestration requires either of two G1 CDKs: Pho85 or Cdk1 (Mazanka and Weiss 2010).…”
Section: Regulation Of Septation Machinery and The Cytokinetic Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The localization of Ace2p is controlled throughout the cell cycle, and for most of the cycle the protein is excluded from the nucleus because of phosphorylation by Cdc28p (O'Conallain et al 1999); in late M, the protein accumulates specifically in the nucleus of the daughter cell, the Ace2p targets are transcribed, and cell separation occurs. Cbk1p is also localized transiently to the nucleus of the daughter cells and this localization is concomitant with and dependent upon that of Ace2p (Colman-Lerner et al 2001;Weiss et al 2002;Nelson et al 2003;Jansen et al 2006;Bourens et al 2008). A combination of genetic and biochemical studies have shown that Cbk1p phosphorylates the Ace2p nuclear export sequence (NES), disrupting its interaction with the nuclear exportin Crm1p and resulting in the accumulation of Ace2p in the nucleus (Bourens et al 2008;Mazanka et al 2008;Sbia et al 2008;reviewed in Parnell and Stillman 2008).…”
mentioning
confidence: 99%